Mutations in genes underlying atypical familial mycobacteriosis are not found in tuberculosis patients from Siberian populations. Issue 2 (March 2015) - Rudko, Alexey A.; Garaeva, Anna F.; Bragina, Elena Yu.; Babushkina, Nadezda P.; Kolokolova, Olga V.; Lipaenkova, Olga N.; Puzyrev, Valery P.; Freidin, Maxim B.
Summary Objectives Atypical familial mycobacteriosis (AFM, OMIM #209950) is caused by mutations in genes regulating IL12/IFNG pathway. Some of the mutations exhibit incomplete penetrance, and they have been proposed to be involved in the common (polygenic) predisposition to tuberculosis (TB). We set out to test this hypothesis in two populations from Siberian region of Russia with high prevalence of TB. Material and methods The prevalence of twelve mutations in IL12/IFNG pathway genes of were analysed in 331 Russians and 238 Tuvinians TB patients and in 279 healthy Russians and 265 healthy Tuvinians. A screening for new mutations and rare polymorphisms was carried out in 10 children with severe generalized TB and severe BCG-vaccine complications using Sanger's bidirectional sequencing. Results Twelve mutations most commonly identified in AFM patients appeared to be "wild-type" monomorphic in the studied groups. No new mutations or rare polymorphisms were identified by sequencing. However, 15 common single nucleotide polymorphisms were found, none of which was associated with TB after correction for multiple testing. Conclusion The results of the study contradict with a hypothesis that mutations underlying AFM syndrome are involved in the predisposition to TB.